Determination of lingual vascular canals in the interforaminal region before implant surgery to prevent life‐threatening bleeding complications. Issue 2 (26th November 2012) - Kilic, Erdem; Doganay, Selim; Ulu, Murat; Çelebi, Nükhet; Yikilmaz, Ali; Alkan, Alper
Abstract Objectives Profuse hemorrhage and airway obstruction may occur during or after the implant surgery in the interforaminal region. The prevention from this complication requires identifying the location of the mandibular lingual vascular canals (MLVCs). The purpose of this study was to evaluate the anatomical variations of MLVCs and to determine the safety margins for implant placement in interforaminal region. Materials and methods Computer tomography (CT) images of 200 consecutive patients were reexamined retrospectively by a radiologist and a maxillofacial surgeon to evaluate the presence of the MLVCs entering the mandible. The diameter and the number of the canals, the distance between the entrance of the canal and mandibular midline, and the height of the entrances of the canals from the inferior mandibular margin were measured. Results Two hundred and thirty‐six median lingual canals (MLCs) and 159 lateral lingual canals (LLCs) were found in 200 patients. Significant differences were found between the number of lingual canals in the midline and canine regions (P < 0.001). Conclusion There is a potential risk of complications due to the injuries of the vessels entering the lingual cortical bone through a number of bone canals during implant placement in the interforaminal region.